Implementation of Management in Enhancing the Quality of Education: A Case Study of Pesantren in Bogor Regency (2019-2023) - Nugraha, Acep; Rahim, Husni; Nata, Abuddin (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This research is motivated by the persistent challenges in educational management within pesantren, which have not yet fully addressed the demands of modern educational quality standards. The study aims to analyze the implementation of management practices in improving the quality of education across traditional, hybrid, and modern pesantren in Bogor Regency. Employing a qualitative method with a descriptive approach, data were collected through interviews, observations, and document analysis. Sources of data included pesantren leaders, teachers, students (santri), and parents. The findings reveal that the typological differences among pesantren shape distinct patterns of management and educational quality: traditional pesantren emphasize spirituality, hybrid pesantren combine religious tradition with formal education, while modern pesantren adopt professional systems. The conclusion highlights that adaptive management practices significantly influence educational quality while simultaneously shaping the institutional identity of pesantren.